The effect of implementation of animated video on online learning during the covid-19 pandemic on students science learning outcomes - Zulkifli Adji Busdayu; I Putu Artayasa; Kusmiyati Kusmiyati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
This study aims to determine the effect of implementing animated video on online learning during the COVID-19 pandemic on students' science learning outcomes in class VIII of SMP Negeri 3 Mataram. This research is a Quasi Experiment with Posttest-Only Control Group design. The research sample was class VIII students at SMP Negeri 3 Mataram consisting of 20 students for the control class and 20 students for the experimental class. The research data was obtained from the learning outcomes test (posttest score) on the respiratory system learning material. Data analysis in this study used the t-test with two independent samples. The results of data analysis showed that there were differences in the posttest mean scores between students who used animated video in the experimental class and students who used conventional learning in the control class. The average posttest value in the experimental class is 68.25, while the posttest average value in the control class is 53. The significance value of the two independent sample t-test is 0.009, meaning that the significance value is smaller than 0.05 (p- value < 0.05), so Ho is rejected. The conclusion of the study is that there is an effect of implementing animated video in online learning during the COVID-19 pandemic on the science learning outcomes of class VIII students at SMP Negeri 3 Mataram. Animated video have a positive effect on student learning outcomes